2019
DOI: 10.1016/j.foodchem.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and antimicrobial properties of a shrimp demineralization extract blended with chitosan as wrapping material in ready-to-eat raw salmon

Abstract: A shrimp extract (SME) obtained from the mild-acid demineralization treatment of shrimp shells to produce chitosan was collected. It was mainly composed of fat (≈73%), protein (≈19%), and ash (≈9%) and contained considerable amounts of calcium (≈1.9 g/100 g), astaxanthin (≈30 mg/100 g) and unsaturated fatty acids (≈27% MUFA, ≈39% PUFA). The SME was used in combination with chitosan for wrapping raw salmon to produce a ready-to-eat product enriched in calcium. No significant changes in hardness were found, as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Chitosan-based coatings prevented the increase of bacteria during the storage of cod patties (López-Caballero et al, 2005), prawns (Arancibia et al, 2015a), and salmon (Gómez-Estaca et al, 2019). Especially striking is the effect of chitosan on H2Sproducers, with counts below the detection limit (< 2 log CFU/g) during the whole period, while Control and GA batches exceed 8 log CFU/g (Figure 4D).…”
mentioning
confidence: 96%
“…Chitosan-based coatings prevented the increase of bacteria during the storage of cod patties (López-Caballero et al, 2005), prawns (Arancibia et al, 2015a), and salmon (Gómez-Estaca et al, 2019). Especially striking is the effect of chitosan on H2Sproducers, with counts below the detection limit (< 2 log CFU/g) during the whole period, while Control and GA batches exceed 8 log CFU/g (Figure 4D).…”
mentioning
confidence: 96%
“…When shrimp shell extract was used in combination with chitosan to package salmon, the experimental results showed that compared to uncoated salmon, there was a significant change in the content of bioaccessible calcium and bioaccessible fat in the test group, although there was no significant change in hardness. In terms of bacterial testing, the total viable counts, pseudomonas, enterobacter, and specific fish humus were found to decrease by 2to 4 log CFU/g during the chilled storage period (5°C, 19 days) in packaged salmon compared to unpackaged salmon 98,110 . Furthermore, chitosan has been combined with the natural product quercetin, black soybean seed coat extract, and grapefruit seed extract to prepare a composite film, and the properties of this film were verified by physical, chemical, and biological methods.…”
Section: Applications Of Chitosan Films In Food Industrymentioning
confidence: 98%
“…Despite this, crustacean waste is a very relevant source of astaxanthin because the processing industry produces large amounts of cephalothorax and carapace residues (40–50% ( w / w ) in weight) containing astaxanthin [ 27 ]. The most common valorization option is probably obtaining chitin/chitosan, but other compounds of industrial interest, such as proteins, lipids, carotenoids, flavor compounds, or calcium carbonate, can be obtained as well [ 28 , 29 ].…”
Section: Astaxanthin: a Valuable Marine Resourcementioning
confidence: 99%